Enhancing Reflective Practice Through Alternative Assessment - Lynn R. Nelson; Frederick D. Drake (Journal of Research in Rural Education, 1997)
Rural educators are asked to meet multiple and sometimes conflicting demands: to raise academic standards, teach basic skills, teach students to be good citizens, and prepare studentsforjobs. Alternative assessment strategies, grounded in reflective practice, have the possibility to enliven instruction and improve students' knowledge, reasoning, and communication skills. The following article suggests that alternative assessment is consistent with the development ofthe knowledge and dispositions associated with critical democratic citizenship. A rubric and alternative assessment example is provided for teachers to incorporate this strategy into their classroom instruction.